The effect of DNA-dependent protein kinase on adeno-associated virus replication. - Young-Kook Choi; Kevin Nash; Barry J Byrne; Nicholas Muzyczka; Sihong Song (PLoS ONE, 2010)
DNA-dependent protein kinase (DNA-PK) is a DNA repair enzyme and plays an important role in determining the molecular fate of the rAAV genome. However, the effect this cellular enzyme on rAAV DNA replication remains elusive.In the present study, we characterized the roles of DNA-PK on recombinant adeno-associated virus DNA replication. Inhibition of DNA-PK by a DNA-PK inhibitor or siRNA targeting DNA-PKcs significantly decreased replication of AAV in MO59K and 293 cells. Southern blot analysis showed that replicated rAAV DNA formed head-to-head or tail-to-tail junctions. The head-to-tail junction was low or undetectable suggesting AAV-ITR self-priming is the major mechanism for rAAV DNA replication. In an in vitro replication assay, anti-Ku80 antibody strongly inhibited rAAV replication, while anti-Ku70 antibody moderately decreased rAAV replication. Similarly, when Ku heterodimer (Ku70/80) was depleted, less replicated rAAV DNA were detected. Finally, we showed that AAV-ITRs directly interacted with Ku proteins.Collectively, our results showed that that DNA-PK enhances rAAV replication through the interaction of Ku proteins and AAV-ITRs.